Students’ perception on the use of Undercover Game to enrich their vocabulary mastery at the Seventh-Grade of SMPN 10 Padang - Rizki, Muhammad; Rani, Yati Aisya (Universitas Negeri Padang, 2025)
This study aims to find out students’ perceptions about using the Undercover Game to learn English vocabulary at SMPN 10 Padang. The research used a descriptive-qualitative method. The participants in this study were 30 seventh-grade students in the 2024/25 academic year who had been using the game for one semester. Data was collected through 1-4 scores Likert-scale questionnaires completed by 30 respondents and followed by interview with 6 respondents. The five indicators of effectiveness, advantages, disadvantages, motivation, and interest regarding the use of Undercover Game. The results showed that students’ perceptions were mostly positive, with an average score of 3.028. It means they think game helped them understand word meanings, learn new vocabulary, feel more motivated, and enjoy the learning process. From the interviews conducted, almost all participants said that this game helped them learn English vocabulary. 3 out of 5 participants confirmed that this game made the learning process more exciting and helped them overcome boredom. Meanwhile, there are 2 participants felt the game did not help them or made them confused. The study suggests that the Undercover Game can be used as another way to teach English vocabulary, with better explanation the rules of the game before playing it.